A simple questionnaire to detect chronic kidney disease patients from Long An province screening data in Vietnam - Huong T. B. Tran; Thu T. N. Du; Nhat D. Phung; Ninh H. Le; Toan B. Nguyen; Hai T. Phan; De T. Vo; Edgar L. Milford; Sinh N. Tran (BMC Research Notes, 2017)
Abstract Background The prevalence of chronic kidney disease (CKD) in rural Vietnam is unknown. We wished to determine the prevalence of CKD and determine whether a simple questionnaire was able to detect individuals at high risk of CKD before expensive confirmatory laboratory testing. Methods A cross sectional study was performed. We recruited 2037 participants from 13 communes of Long An province, Vietnam, for CKD screening with urine albumin/creatinine ratio (ACR) measured by immunoturbidimetric method and serum creatinine to estimate glomerular filtration rate (eGFR). CKD was defined as either ACR ≥ 30 mg/g or eGFR MDRD < 60 ml/min/1.73 m2. A two page questionnaire with 23 variables was administered to each participant with queries postulated to be correlated with risk of CKD. Results Of the 2037 participants, 260 (12.76%) were found to have CKD. Five questionnaire variables (age more than 50, measured hypertension, history of diabetes, history of hypertension, and history of a low salt diet) were correlated with CKD, and used to construct a risk score for CKD. Conclusions CKD is common in Vietnam. Our questionnaire and risk score tool can be used to detect individuals with a higher likelihood of CKD, and who can then be more economically screened with routine laboratory confirmatory tests.